A avaliação dos pacientes internados em Unidade de Terapia Intensiva adulto por condição sensível à atenção primária, por meio do emprego do Primary Care Assessment Tool (PCATool) - Renata Melgaço Gonçalves (2017)
Primary Health Care (PHC), when strengthened and adequately structured, may have significant impacts on secondary and tertiary health care, and may influence the evolution of the initial clinical picture, avoiding worsening of health problems and possible hospitalizations of medium and high complexity. Primary Care Sensitive Conditions (PCSC) are health problems handled by actions which are typical of the first level of attention and whose evolution, in the absence of timely and effective attention, may require hospitalization. The objective of this study was to evaluate Primary Health Care attributes in patients hospitalized in intensive care (ICU) beds for PCSC, through the application of the Primary Care Assessment Tool (PCATool) form, to those admitted to the ICU from March to September / 2016. This was a cross-sectional and descriptive study composed of 303 patients, 163 (53.8%) males. The ageof the interviewees ranged from 26 to 93 years, with a higher prevalence of patients aged 60 years or older (n = 177, 58.42%). Patients were mainly from the city of Belo Horizonte (n = 192, 63.37%). Most prevalent diseases belonged to the group named angina by Ministry of Health PCSC classification of hospitalizations (78.88%). Of results by attribute, only first contact access: utilization presented favorable evaluation (80.5% with a score greater than 6.6). In a bivariate analysis sought to evaluate the influence of sociodemographic data in the attributes scores, it was verified that the gender variable was positively associated with theattributes longitudinality (p = 0.03), coordination: integration of care (p = 0.013) and coordination: information systems (p = 0.02). In the age variable, only the first contact access attribute: utilization, with the group of 60 years or more presenting a score higher than 6.6 in 88.1% of respondents. Regarding the place of consultation, it is possible to show that the outpatient center stood out in the attribute of first contact access: use, which is related to relying on a health service as a source of care for each new problem. When evaluating the variable Diabetes Mellitus (DM), it can be observed that the patients with this pathology had, in general,a worse evaluation of the attributes, and there was statistical significance in the attribute coordination: information systems (p = 0.016). It was possible to conclude that the evaluation of the PHC attributes by a population of patients seen in a UTI of a large hospital in Belo Horizonte, by PCSC, was generally not considered adequate according to the questionnaire employed